AHAMEFULA GENDER COMPLEMENTARITY IN LEADERSHIP: A CASE FOR GENDEROCRACY - Ephraim Ahamefula Ikegbu (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
Most developing and third world countries are deeply engrossed with patrilineal form of leadership which is male-dominated. Any system of government that does not accommodate all segments of the society cannot be seen to be globally accepted especially in this age of consciousness on human rights, justice and rule of law. This paper "Ahamefula: Gender complementarity in leadership: A case for Genderocracy” seeks to argue that the hitherto non-existing balance in the distribution of responsibility and rewards can only divide the state than be a unifying factor. It argues further that, in the new leadership regime it will ignore western contacts but ensure African (Nigeria) ideal form of leadership as its own identity-“ejiri mara”, for unity, cooperation and integration of all genders. This paper is of the opinion that power/ leadership rotation between the genders which in this context, called “genderocracy” be applied as a possible means of reducing waste, maiming, thuggery and others. Genderocracy does not imply inclusiveness in leadership. Inclusion in this context, implies integration or accommodation in the scheme of things by the race, gender, class and region that is in charge of political portfolio. Inclusive participation puts one in a beggarly disposition. It does not offer one equality of rights, as the person accommodated or integrated into the whole class recognizes existing limitations. On the other hand, the thesis of genderocracy rests squarely on a philosophical assumptive matrix of rotation and/or power sharing for and among the genders on equal parameter disregarding any form of parochial and primordial sensibilities. The paper shall apply rational, analytic and expository methods. The objectives of the paper is to design a model of leadership which has the capacity of ensuring good governance and equal participation. The concern of the paper is to propagate a novel leadership platform or model for Nigeria of Africa